Peran Guru Fiqih dalam Pembiasaan Keaktifan Shalat Berjamaah Siswa Madrasah Aliyah Negeri 1 Kulon Progo, Yogyakarta - Miftakul Azis; Muh. Mustakim (Indonesian Journal of Teaching and Teacher Education, 2023)
Teachers have an important role in the habituation of the implementation of Islamic teachings. Islamic Religious Education aims to prepare pious individuals who carry out Islamic religious teachings, and to prepare individuals who understand Islam (mutafaqqih fiddin). This study aims to find out the role and strategy of the fiqh teacher in increasing the activity of congregational prayers at Madrasah Aliyah Negeri (MAN) 1 Kulon Progo, D.I. Yogyakarta. This study used a descriptive qualitative research method. The subjects of this study were Head of MAN 1 Kulon Progo, Fiqh teachers of MAN 1 Kulon Progo, and the students of MAN 1 Kulon Progo. Data collection was carried out by observation, in-depth interviews, and documentation to complement the data obtained from observations and interviews. The data validation was used source triangulation and technical triangulation, while data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the research show that the role of the fiqh teacher in the activeness of congregational prayers of MAN 1 Kulon Progo students is as an activator, someone who encourages students to pray in congregation; and the fiqh teacher also acts as a companion for students in conducting congregational prayers. The strategy of the fiqh teacher in increasing the activity of congregational prayers of MAN 1 Kulon Progo students are the fiqh teacher applies the habituation method; special guidance methods; and the teacher has not applied the method of punishment or sanctions.